Kalif bocian i inne opowiadania - Hauff, Wilhelm, 1802-1827.; Lewandowski, Artur (Warszawa : Votum, 1992)
A selection of fairy tales about the East by a noted German author. Ages 8-12.
Translation of: Kalif Storch.